Experimental reflex pulmonary atelectasis: noxious reflexes to vascular starting point. Acute bloating as a specific injury - Stajano, Carlos; Scandroglio, Juan José; Passano, M Amelia (Cirugía del Uruguay, 2020)
Presented at session 7th May 1952